State of World Population 2004 - United Nations Population Fund (United Nations, 2004)
This year’s report examines countries’ achievements and constraints in implementing the Cairo consensus, including efforts to improve the quality and reach of reproductive health programmes, promote women’s rights, improve maternal and child health and strengthen HIV prevention efforts. UNFPA’s report makes the case that mobilizing political will and increased funding by the international community is crucial if countries are to maintain and build on the gains of the past decade.